Analisis Pola Konsumsi Pangan Berdasarkan Status IPM di Jawa Timur - Mayasari, Dewi; Satria, Dias; Noor, Iswan (UI Scholars Hub, 2018)
The objectives of this article are (1) to analyze the influence of socio economic characteristics in influencing patterns of food consumption by HDI and (2) Analyze demand responses (elasticity) of East Java household to food prices and income changes. Linear Approximation Almost Ideal Demand System (LA/AIDS) and elasticity are used to answer the objectives by using microdata Susenas 2016. The result indicates that generally, socio economic characteristics contribute substantially in determining household food consumption patterns and based on their elasticity values, food commodities in East Java are price inelastic and more responsive to income changes.